2005
DOI: 10.1111/j.1439-0388.2005.00517.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of calpastatin (CAST/MspI) polymorphism with meat quality parameters of fatteners and its interaction withRYR1genotypes

Abstract: The aim of this study was to analyse the effect of polymorphism of calpastatin (CAST) and RYR1 genes for some meat quality traits taking into consideration the group of meatiness and their mutual interactions. Investigations were carried out on a group of 201 fatteners which were crosses of four breeds. The results obtained show that CAST/MspI genotype has an effect close to the major effect for drip loss from LL muscle tissue at 48 h as well as at 96 h postmortem (0.92 and 0.96 SD respectively). Among the mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 23 publications
1
15
0
1
Order By: Relevance
“…However, no positive effect of the (Tables 3 and 5), which corroborates the findings pointing to the negative effect of the T allele on meat quality (Oliver et al 1993;Biedermann et al 2000) but is not confirmed in the study of , which shows a similar meat quality of the pigs of CC and CT genotypes. Furthermore, no interaction was found between the meatiness range and RYR1 genotype in the hybrid pigs in relation to meat quality traits, which was also observed by Krzęcio et al (2005) in a study on pigs with 25% of Pietrain breed and by Rybarczyk et al (2006) in a study on pigs with 50% of Pietrain breed in the genotype. In the present study, a significant interaction (P ≤ 0.05) was found between RYR1 genotype and carcass meatiness range in mean backfat thickness from five measurements and intramuscular fat content.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…However, no positive effect of the (Tables 3 and 5), which corroborates the findings pointing to the negative effect of the T allele on meat quality (Oliver et al 1993;Biedermann et al 2000) but is not confirmed in the study of , which shows a similar meat quality of the pigs of CC and CT genotypes. Furthermore, no interaction was found between the meatiness range and RYR1 genotype in the hybrid pigs in relation to meat quality traits, which was also observed by Krzęcio et al (2005) in a study on pigs with 25% of Pietrain breed and by Rybarczyk et al (2006) in a study on pigs with 50% of Pietrain breed in the genotype. In the present study, a significant interaction (P ≤ 0.05) was found between RYR1 genotype and carcass meatiness range in mean backfat thickness from five measurements and intramuscular fat content.…”
Section: Resultssupporting
confidence: 60%
“…The analysis of meat quality and its basic chemical composition showed significant differences only in meat water-holding capacity (WHC), which was favourably higher in the carcasses with meatiness below 54% (P ≤ 0.05). Krzęcio et al (2005) showed a negative effect of higher carcass meatiness on meat quality. On the other hand, Rybarczyk et al (2006) did not find any differences in meat quality and its chemical composition according to carcass meatiness level in their studies on pigs from sows of white breeds and Pietrain boars.…”
Section: Resultsmentioning
confidence: 99%
“…Also and Kurył et al (2004), who studied crossbreds sired by Duroc × Pietrain boars, failed to demonstrate a relationship between the CAST/MspI genotype and meat quality traits, except for loin efficiency during smoking. Krzęcio et al (2005), on the other hand, observed significant effects of the CAST/MspI polymorphism on the level of lactic acid in the longissimus lumborum muscle tissue 45 minutes post mortem, index of energy metabolism intensity R 1 , water holding capacity (WHC), drip loss from muscle tissue at 48 and 96 hours post mortem, as well as meat protein and water content. Moreover, demonstrate that polymorphism at the locus CAST/MspI relatively strongly correlates with the incidence of increased drip loss from meat in the group of pigs with the gene RYR1 T .…”
Section: Discussionmentioning
confidence: 99%
“…Kusec et al (2005) did not observe significant differences in butchery value of carcasses between the CC and CT pigs; the authors found, however, that meat quality of heterozygous pigs (CT) was worse. Also Krzęcio et al (2005) and Kuhn et al (2005) report poorer quality of meat obtained from CT pigs. On the other hand, Koćwin-Podsiadła et al (2003) did not find significant differences in meat quality between the discussed RYR1 genotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation